2011
DOI: 10.1007/s11802-011-1764-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carboxymethyl-chitosan on wound healing in vivo and in vitro

Abstract: Effects of carboxymethyl-chitosan with different molecular weights on wound healing were investigated in vivo and in vitro. A second degree burn model was performed in rats and the accelerative effects of carboxymethyl-chitosan on wound repair were observed. Contents of transforming growth factor (TGF)-β1,interleukin(IL)-6 and matrix metalloproteinase (MMP)-1 in wounds were determined by enzyme-linked immunosorbent assay (ELISA). In vitro study evaluated the influence of carboxymethyl-chitosan on cytokines sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Several in vivo studies also have proved nontoxicity and good biocompatibility of CM‐chitosan . These beneficial biological properties make CM‐chitosan widely assessed in the biomedical material fields in vivo, such as drug delivery systems, plastic surgery, tissue engineering, and wound‐healing materials . The results of this study suggest that CM‐chitosan might offer a biocompatible and flexible platform for designing coatings to protect silicone surfaces from infection.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Several in vivo studies also have proved nontoxicity and good biocompatibility of CM‐chitosan . These beneficial biological properties make CM‐chitosan widely assessed in the biomedical material fields in vivo, such as drug delivery systems, plastic surgery, tissue engineering, and wound‐healing materials . The results of this study suggest that CM‐chitosan might offer a biocompatible and flexible platform for designing coatings to protect silicone surfaces from infection.…”
Section: Discussionmentioning
confidence: 64%
“…[33][34][35][36] These beneficial biological properties make CM-chitosan widely assessed in the biomedical material fields in vivo, such as drug delivery systems, 36 plastic surgery, 37 tissue engineering, 38 and wound-healing materials. 39 The results of this study suggest that CM-chitosan might offer a biocompatible and flexible platform for designing coatings to protect silicone surfaces from infection. Furthermore, recent studies showed that chitosan-coated surfaces have antibiofilm properties against bacteria and fungi in vitro.…”
Section: Discussionmentioning
confidence: 80%
“…Different types of wound healing scaffolds were prepared from naturally derived and synthetic polymers, of which the natural polymers serve better due to their unique biological adaptive properties . Nowadays, bio and synthetic polymer based wound dressings like nanocomposites, composite films, hydrogels, nanofiber mats with the incorporation of growth factors and drugs were fabricated . The attraction on biopolymers towards tissue engineering was owing to the biocompatible, bio‐degradation, non‐toxic and antimicrobial properties.…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] Nowadays, bio and synthetic polymer based wound dressings like nanocomposites, composite films, hydrogels, nanofiber mats with the incorporation of growth factors and drugs were fabricated. [7,8] The attraction on biopolymers towards tissue engineering was owing to the biocompatible, bio-degradation, non-toxic and antimicrobial properties.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it can promote the adhesion, growth and reproduction of fibroblasts in vitro (34) and in vivo (35). It can also promote skin wound healing (36). Scaffolds based on Gel and CMCS for dermal tissue engineering have been studied (37).…”
Section: Introductionmentioning
confidence: 99%